KUALITAS PELAYANAN SURAT PERINTAH PENCAIRAN DANA DI BIDANG PERBENDAHARAAN DINAS PENDAPATAN PENGELOLAAN KEUANGAN DAN ASET DAERAH KABUPATEN SIGI - Abdullah, Abdullah (Katalogis, 2016)
This study aimed to describe the Quality of Service Fund Disbursement Order in Treasury Sector Financial Management Revenue and Asset Sigi. The research method used was qualitative .. To get more in-depth information in this study determined the informant with Porpusive Sampling technique and who became informants in this study is the Head of Treasury, Treasury Employees in the Field, and the service user. Sources of data in this study are primary data and secondary data. Data Collection Techniques done by observation, interview and documentation. Analysis of the data in this study is the reduction Data, Data Presentation, Withdrawal Conclusions and Verification, Eligibility Checking Data. The results of this study describes the Quality of Service Fund Disbursement Order in Sector Treasury Management Revenue Finance and Asset Blood Sigi Regency, based on research results have not been implemented to the fullest. This is evidenced by five indicators used as a benchmark in the study focused only two studies were met and that the indicator responsiveness (responsiviness) and indicators of empathy (empathy). Meanwhile, other indicators such as Tangibles (physical evidence) is not maximized, Reliability (reliability) have not materialized, and Assurance (guarantees and certainty) is not adequate.